Effect of microwave frying on the physicochemical properties of palm olein and French fries - How, Yu Hsuan; Nyam, Kar Lin; Lee, Xian Wei; Akanda, Md Jahurul Haque; Tan, Chin Ping (John Wiley and Sons Inc, 2024)
This study aimed to evaluate the effect of microwave power and duration on French fries using palm olein. The deep-fat frying was served as a control. The microwave frying of French fries was conducted at low (100 W), medium (600 W), and high (1000 W) for 1, 3, and 5 min. The physicochemical properties of French fries and the quality of palm olein were analyzed. The French fries microwaved at 600 W for 3 min showed comparable hardness (300 g), cohesiveness (0.76), springiness (3.5 mm), adhesion (0.3 mJ), and water activity (0.88 Aw) to deep-fat frying. The palm olein demonstrated lower peroxide and para-anisidine values in microwave frying; while deep-fat frying had lower total polar compounds in frying oil and lower oil content in oil extracted from French fries. Nevertheless, the high oxidation stability in terms of peroxide and para-anisidine value in frying oil from microwave frying showed its potential as an alternative frying technique to deep-fat frying.